Apoptosis in T-Lymphocyte Subsets in Human Immunodeficiency Virus-Infected Children Measured Immediately Ex Vivo and following In Vitro Activation - Niehues, Tim (American Society for Microbiology, 2001)
Phosphatidylserine molecules are translocated to the outer plasma membrane of lymphocytes undergoing apoptosis and can be detected by the binding of fluorochrome-conjugated annexin V. Using the annexin V assay, we examined CD4 and CD8 T cells from human immunodeficiency virus (HIV)-infected children for apoptosis upon isolation or following in vitro culture. Immediate ex vivo analysis or overnight culture showed significantly higher levels of apoptosis in CD8 cells than in CD4 cells. Following culture with the activating stimulus phytohemagglutinin or anti-CD3 monoclonal antibody, we observed an increase in the percentage of apoptotic CD4 cells, whereas there was no change in the rate of CD8 cell death. These results demonstrate that in HIV-infected children, CD8 apoptosis may occur at a greater rate than CD4 apoptosis in vivo; greater CD4 depletion may be observed due to more efficient mechanisms for peripheral lymphocyte replacement in the CD8 compartment. Furthermore, our data suggest that CD8 lymphocytes may be maximally activated in vivo, a condition which may lead to the exhaustion of CD8-mediated immunity. These findings clarify the differences between the CD4 and CD8 apoptotic responses to HIV.